Association of environmental tobacco smoke exposure with socioeconomic status in a population of 7725 New Zealanders. Issue 3 (1st September 1998) - Whitlock, Gary; MacMahon, Stephen; Vander Hoorn, Stephen; Davis, Peter; Jackson, Rodney; Norton, Robyn
Abstract : OBJECTIVE: To test the hypothesis that environmental tobacco smoke (ETS) exposure is inversely associated with socioeconomic status. DESIGN: Survey. SETTING: General community, New Zealand. PARTICIPANTS: 7725 non-smoking adults (volunteer sample of a multi-industry workforce, n = 5564; and a random sample of urban electoral rolls, n = 2161), including 5408 males; mean age 45 years. MAIN OUTCOME MEASURES: ETS exposure was assessed as self-reported number of hours per week spent near someone who is smoking, and as prevalence of regular exposure to some ETS. Socioeconomic status was assessed as educational level, occupational status, and median neighbourhood household income. RESULTS: Both measures of ETS exposure were steeply and inversely associated with all three indicators of socioeconomic status (all p<0.0001). Geometric mean ETS exposure ranged from 16 minutes per week among university-educated participants to 59 minutes per week in the second lowest occupational quintile (95% confidence intervals: 14–18 minutes per week and 54–66 minutes per week). The associations with occupational status and educational level were steeper than those with neighbourhood income. The socioeconomic gradients of ETS exposure were steeper among participants aged less than 35 years than among participants aged over 50 years, among men than women, and among Maori than Europeans. CONCLUSIONS: In this study population, ETS exposure was inversely associated with socioeconomic status. Greater ETS exposure might therefore contribute to the higher risks of disease and death among low socioeconomic groups. These results provide a further rationale for targeting tobacco control measures to people in low socioeconomic groups.